A framework for the exergy analysis of future transport pathways: Application for the United Kingdom transport system 2010–2050. (August 2015) - Byers, Edward A.; Gasparatos, Alexandros; Serrenho, André C.
Abstract: Exergy analysis has been used to quantify the historical resource use efficiency and environmental impact of transport systems. However, few exergy studies have explored future transport pathways. This study aims to, (a) develop a conceptual framework for the exergy analysis of multiple future transport and electricity pathways, (b) apply this framework to quantify future resource consumption and service delivery patterns, (c) discuss the policy-relevant results that exergy studies of future transport systems can offer. Multiple transport and electricity pathways developed by the UK Government are used to explore changes in energy use, useful work delivery and greenhouse gas emissions. In passenger transport, ambitious electrification results in a 20% increase of useful work delivery, whilst reducing GHG emissions and energy consumption by 65%. For freight, international shipping and aviation, smaller exergy efficiency improvements make useful work delivery and greenhouse gas emissions highly dependent on transport demand. Passenger transport electrification brings a step-change in useful work delivery, which if accompanied by low-carbon electricity, significantly reduces greenhouse gas emissions. The efficiency of low-carbon electricity systems is significant for useful work delivery, but not dominant across the scenarios explored. High penetration of renewables and electrified transport is the most resource-efficient combination in this context. Highlights: Develop an exergy analysis framework of future transport pathways and apply it to UK. Electrification of personal transport brings step change in useful work delivery. Efficiency of electricity supply becomes significant once transport is electrified. High electrification increases useful work (+20%) and reduces emissions (−65%). High penetration of renewables and electrified transport is most resource efficient.